Spelling Variation in Inner-Circle Englishes - Pacheco-Franco, Marta (Atlantis. Journal of the Spanish Association for Anglo-American Studies, 2023)
English is the language with the largest number of speakers in the world, when both native and non-native speakers are included. With an estimated 1,268 million users around the globe, linguistic variation is bound to occur. Research on World Englishes focuses on the study of this variation, though it has systematically disregarded the linguistic level of orthography. This neglect has operated under the assumption that most contemporary varieties must adhere to British English spelling norms. Nevertheless, recent studies on the Americanisation of English worldwide (Mair 2013; Gilquin 2018; Gonçalves et al. 2018) have brought the question of spelling variation back to the fore. The present paper thus analyses the distribution of the most distinctive spelling variants—i.e. -our/-or, -re/-er and -isation/-ization—in the varieties of the inner circle from a synchronic perspective. By means of a corpus-based investigation of English online, this study will outline the spelling usage patterns for the aforementioned varieties and will analyse the highly-likely Americanisation process in spelling on the Internet.